Creating a holistic excellence model adapted for technology-based companies - Tejedor,Ana Clara Pastor (2014)
The objective of this study is the preparation of a management model that brings together the advantages of models from different disciplines: Balanced Scorecard (BSC), European Foundation for Quality Management (EFQM) and Holistic Marketing (HM). HM proposes an overview of organisations - taking into account all value streams which companies generate - while the business excellence criteria of the EFQM define the structure platforms of Kotler et al. (2001), and the BSC guarantees implementation, monitoring and enforcement. Once developed, this model was adapted for the specific characteristics of technology-based companies (TBC), based on interviews with managers of these businesses.